Murder by Christmas : 25 days to solve the crime - Jessup, Joel (Michael O'Mara Books, Limited, 2025)
"Mr. Holly is dead, and everyone in the village could be a suspect. Can you solve the advent calendar of puzzles to figure out whodunnit before Christmas Day? Welcome to the quiet English village of Candlestow, where the festive season is in full swing. The residents are busy preparing for Christmas when a local resident - Mr. Holly - is found dead at a rehearsal for the annual Christmas play. Team up with the local detective, Inspector Twelvetrees, as you try to crack the curious case. The plot twist? On December 1, a clue arrives at the police station and reveals a dark secret from one of the village's inhabitants. Someone is taking revenge on the village, and everyone is a potential target. And so it goes: every day, a new clue arrives, and a new dark secret is revealed. Can you solve the case of the mysterious advent-calendar conundrums by cracking 25 puzzles? And can you uncover the biggest puzzle of all: who killed Mr. Holly?"